Well posedness and comparison principle for option pricing with switching liquidity. (October 2018) - Gyulov, T.B.; Vulkov, L.G.
Abstract: We consider an integro-differential equation which is derived from a system of coupled parabolic PDE and an ODE and describes an European option pricing with liquidity shocks. We study the well-posedness and prove comparison principle for the corresponding initial value problem.